Relative validity of a mobile AI-technology assisted dietary assessment in adolescent females in Vietnam - Nguyen, Phuong Hong; Koch, Bastien; Arrieta, Alejandra; Gelli, Aulo; Tran, Lan Mai; Hoang, Nga Thu (Elsevier, 2022)
Background: There is a gap in data on dietary intake of adolescents in low- and middle-income countries. Traditional methods for dietary assessment are resource intensive and lack accuracy with regards to portion size estimation. Technology assisted dietary assessment tools have been proposed but few have been validated for feasibility of use in LMICs. Objectives: We assess the relative validity of FRANI (Food Recognition Assistance and Nudging Insights), a mobile Artificial Intelligence (AI) application for dietary assessment in adolescent females (n = 36) aged 12–18y in Vietnam, against weighed records (WR) standard, and compared FRANI performance to a multi-pass 24-hour recall (24HR).